Migraine attack diary as an indicator of hypomanic turn - Ciriaco, Jovana; Brandão, Vinícius Andreata; Brum, Ranielly Correa Lube Santos; Carlini, ⁠Juliana Tancredo; Rosario, Natália Lamas; Caetano, Maria Clara de Castro e; Moreira, Karimy Patrícia Melgaço; Medeiro, Vinícius de Pádua Sanders; Kersanach, Betina Bolina; Pina, Eduarda Ferro Firme (Headache Medicine, 2024)
INTRODUCTION Migraine, a common neurological disorder, often coexists with mood disorders such as bipolar disorder type II (BDII). The link between migraine and mood swings in BDII patients is well-documented. Literature suggests migraine and BD share neurobiological mechanisms, including mitochondrial dysfunction and neurotransmitter abnormalities. Studies also indicate mood swings can trigger migraines in BD patients OBJECTIVE This report aims to elucidate the interplay between migraine and mood disorders, specifically BDII, in a 25-year-old female patient. CASE REPORT A 25-year-old black female student began experiencing visual aura episodes at 16, progressing to headaches at 18, characterized by right-sided pulsatile pain, nausea, fatigue, photophobia, phonophobia, osmophobia, irritability, psychomotor slowness, and difficulty concentrating. She was diagnosed with migraine with aura in 2017 and initially treated with amitriptyline, discontinued due to intolerance. She managed symptoms thereafter with dihydroergotamine mesylate, dipyrone monohydrate, and caffeine. In 2022, seeking psychiatric care for worsening symptoms, she was diagnosed with generalized anxiety disorder, starting fluvoxamine and later lamotrigine for mood swings. By January 2023, her migraines intensified alongside a hypomanic episode and two depressive episodes with suicidal thoughts, leading to a diagnosis of bipolar disorder type II (BDII) and treatment with lithium carbonate 600 mg. Since early 2023, she meticulously recorded mood and headache occurrences, identifying correlations between her headaches and mood cycles. Over 487 days, she documented 71 pain days from 31 headache attacks, coinciding notably with 17 of the 71 pain days (24%) during hypomanic episodes, where headaches preceded two episodes by two days. During depressive periods, 9 of the 71 pain days (13%) occurred, with headaches present in the final five days of two episodes.Parte superior do formulário Parte inferior do formulário CONCLUSION This case underscores the complex interaction between migraine and BDII, raising the question of whether migraines might act as a prodrome or trigger for mood cycling rather than just a consequence. The findings in the literature and this case emphasize the need for therapeutic approaches that consider the interaction between BDII and migraine for optimal clinical management and improved patient quality of life.